Scientific and production substantiation of the effectiveness of the product for dry hoof baths - Tarasova Evgenya; Khuzin Damir; Mingaleev Danil; Yusupov Sultan; Potekhina Ramziya; Bykova Polina; Lukina Guliya; Erokhondina Marina; Tremasova Anna (BIO Web of Conferences, 2024)
This paper presents the results of a study of the adsorption activity of a developed complex product for the treatment and prevention of diseases of the distal extremities of cattle and its effectiveness with individual and group use using the method of dry hoof baths in a number of agricultural enterprises with tethered and freestall housing of cattle. It was shown that the developed product has a porous structure and a wide range of adsorption. The main cause of infection causing mass lesions of the fingers and hooves of cattle in the surveyed agricultural enterprises was an increase in the threshold number of the diversity of saprophytic and opportunistic microorganisms transmitted directly from one animal to another. Associations of bacteria and micromycetes determined the cause of the occurrence and spread of infectious diseases of the fingers and hooves. The test results of the developed complex product, which includes inorganic adsorbents and active substances with pronounced fungicidal, bactericidal and anti-inflammatory properties indicate the possibility of its introduction into the system of control measures with diseases of fingers and hooves in disadvantaged agricultural enterprises with both tethered and free-stall livestock keeping.